2004
DOI: 10.1002/chem.200400320
|View full text |Cite
|
Sign up to set email alerts
|

Selection of a Pentameric Host in the Host–Guest Complexes {[{[P(μ‐NtBu)]2(μ‐NH)}5]⋅I}[Li(thf)4]+ and [{[P(μ‐NtBu)]2(μ‐NH)}5]⋅HBr⋅THF

Abstract: The structures of the host-guest complexes [[[[P(mu-NtBu)]2(mu-NH)]5]I]-.[Li(thf)4]+ [2.I[Li(thf)4]] and [[[P(mu-NtBu)]2(mu-NH)]5].HBr.THF (2.HBr.THF) show that increased distortion of the framework of the pentameric macrocycle [[[P(mu-NtBu)]2(mu-NH)]5] (2) occurs with the larger halide ions. Theoretical studies show that the thermodynamic stabilities of the model host-guest anions [2.X]- (X=Cl, Br, I) are in the order Cl- approximately Br->I-, that is, the reverse of the templating trend observed experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
28
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 16 publications
0
28
0
Order By: Relevance
“…[8] The greater proportion of the cis isomer of 1 over the trans may have an influence on the formation of a macrocyclic (rather than oligomeric or polymeric) product. [1,3,4] Owing to the low solubility of the macrocycle 2 in organic solvents (such as CHCl 3 , toluene, and THF), further elucidation of the chemical environments and bonding of the Se atoms in its macrocyclic backbone using 77 Se NMR spectroscopy was not possible. This situation, and the fact that only the dimer [(Se=)P(mNtBu) 2 P(m-Se)] 2 + could be observed in the positiveion electrospray mass spectrum of 2 (m/z 726), meant that the exact nature and size of the macrocycle could not be ascertained prior to its structural characterization.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[8] The greater proportion of the cis isomer of 1 over the trans may have an influence on the formation of a macrocyclic (rather than oligomeric or polymeric) product. [1,3,4] Owing to the low solubility of the macrocycle 2 in organic solvents (such as CHCl 3 , toluene, and THF), further elucidation of the chemical environments and bonding of the Se atoms in its macrocyclic backbone using 77 Se NMR spectroscopy was not possible. This situation, and the fact that only the dimer [(Se=)P(mNtBu) 2 P(m-Se)] 2 + could be observed in the positiveion electrospray mass spectrum of 2 (m/z 726), meant that the exact nature and size of the macrocycle could not be ascertained prior to its structural characterization.…”
mentioning
confidence: 99%
“…The result of this arrangement is that (unlike in 2) there are no available donor atoms for metal coordination within the backbones of these macrocycles. Significantly, in 2 (where there are no organic substituents bonded to the m-Se atoms), a cisoid geometry of the m-Se atoms with respect to the P 2 N 2 rings is adopted (similar to that seen in the related nitrogen-based torocycles [{P(m-NtBu)} 2 (m-NH)] n (n = 4, 5), Scheme 1), [3,4] thus allowing donor Se atoms to be available for potential metal coordination.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[23,24] However, pentameric NH-bridged macrocycles are obtained in the presence of excess of halide ions (X À , particularly I À ) (n = 5). [25,26] The observation of templating in a molecular inorganic system of this type is extremely rare and is directly analogous to macromolecular organic systems. [27,28] It has also been shown that hexameric S-and Se-bridged macrocycles, [E=P(m-N t Bu) 2 P(m-E)] 6 (E = S, Se) (D, Scheme 2) of this class containing alternating P III /P V -skeletons can be readily obtained via the Wurtz-type coupling reactions of the dimers [(Cl)(E = )P(m-N t Bu)] 2 although the yields are low (ca.…”
mentioning
confidence: 99%